Systematic Literature Review on The Influence of Channel Integration on Omni-Channel Customer Loyalty - Dewi Anggraeni; Endang ruswanti; Unggul Kustiawan; Edi Hamdi (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
The rapid evolution of digital technologies and shifting consumer expectations has accelerated the adoption of omnichannel strategies across global retail markets. The effectiveness of these strategies depends greatly on the level of channel integration, which enables seamless transitions across online and offline touchpoints. This systematic literature review synthesizes empirical findings from the past five years to examine how channel integration shapes customer loyalty in omnichannel retailing. The review identifies key mechanisms such as enhanced customer experience, perceived value, trust formation, and cross-channel consistency as critical pathways linking integration to loyalty outcomes. It also highlights relevant theoretical perspectives and emerging mediating and moderating variables. The findings offer theoretical implications by clarifying the mechanisms through which channel integration strengthens loyalty formation, and practical implications by guiding retailers to develop integrated channel strategies that improve customer engagement, satisfaction, and long-term loyalty.